Can we IMPROVE cardiovascular outcomes through phosphate lowering in CKD? Rationale and protocol for the IMpact of Phosphate Reduction On Vascular End-points in Chronic Kidney Disease (IMPROVE-CKD) study. Issue 2 (21st February 2019) - Lioufas, Nicole; Toussaint, Nigel D; Pedagogos, Eugenia; Elder, Grahame; Badve, Sunil V; Pascoe, Elaine; Valks, Andrea; Hawley, Carmel
Abstract : Introduction: Patients with chronic kidney disease (CKD) are at heightened cardiovascular risk, which has been associated with abnormalities of bone and mineral metabolism. A deeper understanding of these abnormalities should facilitate improved treatment strategies and patient-level outcomes, but at present there are few large, randomised controlled clinical trials to guide management. Positive associations between serum phosphate and fibroblast growth factor 23 (FGF-23) and cardiovascular morbidity and mortality in both the general and CKD populations have resulted in clinical guidelines suggesting that serum phosphate be targeted towards the normal range, although few randomised and placebo-controlled studies have addressed clinical outcomes using interventions to improve phosphate control. Early preventive measures to reduce the development and progression of vascular calcification, left ventricular hypertrophy and arterial stiffness are crucial in patients with CKD. Methods and analysis: We outline the rationale and protocol for an international, multicentre, randomised parallel-group trial assessing the impact of the non-calcium-based phosphate binder, lanthanum carbonate, compared with placebo on surrogate markers of cardiovascular disease in a predialysis CKD population—the IM pact of P hosphate R eduction O n V ascular E nd-points (IMPROVE)-CKD study. The primary objective of the IMPROVE-CKD study is to determine if the use of lanthanum carbonate reduces the burden of cardiovascular disease in patients with CKD stages 3b and 4 when compared with placebo. The primary end-point of the study is change in arterial compliance measured by pulse wave velocity over a 96-week period. Secondary outcomes include change in aortic calcification and biochemical parameters of serum phosphate, parathyroid hormone and FGF-23 levels. Ethics and dissemination: Ethical approval for the IMPROVE-CKD trial was obtained by each local Institutional Ethics Committee for all 17 participating sites in Australia, New Zealand and Malaysia prior to study commencement. Results of this clinical trial will be published in peer-reviewed journals and presented at conferences. Trial registration number: ACTRN12610000650099.